The Transformative Effects of Privatization in China : A Natural Experiment Based on Politician Career Concern - Huang, Zhangkai; Liu, Jinyu; Ma, Guangrong; Xu, Lixin Colin (World Bank, Washington, DC, 2020)
The serious implications of privatizing state-owned enterprises for politicians, managers, and investors make such decisions highly contingent on firm characteristics and past performance, complicating the identification of the privatization effects. A unique opportunity for this identification arises from a rule of promotion of local politicians based on age requirements in China. This paper finds that Chinese cities whose top officials were older than age 58 were 20 percent less likely to privatize local state-owned enterprises during the wave of state-owned enterprise restructuring starting in the late 1990s. Relying on the regression discontinuity design, the analysis finds that privatizations led to productivity gains of more than 170 percent, an order of magnitude larger than the traditional estimates based on the firm fixed effect specification (including its random-growth variant). The paper further finds that the privatization effects are significantly larger when the government is less involved in the affairs of local firms. The findings underscore the need to deal with the time-varying selectivity of privatizations and highlight the crucial role that state-owned enterprise privatizations played in China's economic takeoff.